MANAJEMEN KONFLIK DALAM ORGANISASI - Salsabilla Aura Nurhafifi; Mohamad Muspawi; Yuliani Safitri; Rts. Tasya Salsabila (STKIP Subang, 2026)
Conflict in organizations is inseparable from interactions between individuals and groups and has a significant influence on organizational performance. This study aims to examine the characteristics of organizational conflict, the process by which it occurs, the causal factors, its impact on performance, and effective conflict management strategies. The method used is a qualitative approach through literature studies by examining various theories and relevant research results. The results of the study indicate that conflict has two sides, namely it can have positive or negative impacts depending on the type, level of intensity, and how it is managed. Well-managed conflict can improve the quality of decision-making, encourage innovation, and increase productivity. Meanwhile, conflict that is not handled appropriately can reduce performance and damage work relationships. In addition, conflict management as an effort to control organizational conflict includes the process of conflict assessment, interaction management, and selecting appropriate resolution strategies, which include conflict stimulation, conflict reduction, and conflict resolution through various approaches tailored to the conditions of the organization, so that conflict can be directed into a constructive force in supporting the achievement of organizational goals